Pregnant Women's Efforts to Prevent Stunting During Pregnancy at the Akbar Medika Clinic, Mojokerto Regency - Meilinawati SB, Elies (Kirana Publisher (KNPub), 2024)
Stunting is another form of growth failure and chronic malnutrition. Stunting can occur before birth and is caused by very poor nutritional intake during pregnancy, very poor eating patterns, low food quality in line with the frequency of infections so that it can inhibit growth. Stunting prevention is an important priority, especially during pregnancy. The aim of this research is to describe the efforts of pregnant women to prevent stunting during pregnancy at the Akbar Medika Clinic, Mojokerto Regency. The research design used in this research is descriptive. The population was all third trimester pregnant women at the Akbar Medika Clinic, Mojokerto Regency, totaling 30 people, the sampling technique used was a non-probability sampling technique, accidental sampling type, totaling 28 people. The results of this research are that efforts to prevent stunting during pregnancy among pregnant women in the third trimester are mostly good (64.3%). Mother's characteristics and sociodemographics are related to stunting prevention behavior, some of which are age and education. The older the mother gets, the better the knowledge she gets and the better mindset she has, thus making the mother behave well. With higher education, mothers can more easily receive information and are able to apply all things or behavior that are good for their pregnancy.